Differential Susceptibility to Parenting among African American Youths: Testing the DRD4 Hypothesis - Beach, Steven R. H. (2010)
To test the differential susceptibility to parenting hypothesis, a 4-wave, randomized prevention design was used to examine the impact of the Strong African American Families (SAAF) program on past-month substance use across 29 months as a function of DRD4 genotype. Youths (N = 337; M age = 11.65 years) were assigned randomly to treatment condition. Those carrying a 7-repeat allele showed greater differential response to intervention vs. control than those with two 4-repeat alleles. Control youths but not treatment youths with a 7-repeat allele reported increases in past-month substance use across the 29-month study period, but this pattern did not emerge for those with the 4-repeat allele. Supporting the differential susceptibility to parenting hypothesis, the results suggest a greater preventive effect for youths carrying a 7-repeat allele, a role for DRD4 in the escalation of substance use during adolescence, and potential for an enhanced understanding of early-onset substance use.